Morphological characterization of bushy cells and their inputs in the laboratory mouse (Mus musculus) anteroventral cochlear nucleus. - Amanda M Lauer; Catherine J Connelly; Heather Graham; David K Ryugo (PLoS ONE)
Spherical and globular bushy cells of the AVCN receive huge auditory nerve endings specialized for high fidelity neural transmission in response to acoustic events. Recent studies in mice and other rodent species suggest that the distinction between bushy cell subtypes is not always straightforward. We conducted a systematic investigation of mouse bushy cells along the rostral-caudal axis in an effort to understand the morphological variation that gives rise to reported response properties in mice. We combined quantitative light and electron microscopy to investigate variations in cell morphology, immunostaining, and the distribution of primary and non-primary synaptic inputs along the rostral-caudal axis. Overall, large regional differences in bushy cell characteristics were not found; however, rostral bushy cells received a different complement of axosomatic input compared to caudal bushy cells. The percentage of primary auditory nerve terminals was larger in caudal AVCN, whereas non-primary excitatory and inhibitory inputs were more common in rostral AVCN. Other ultrastructural characteristics of primary auditory nerve inputs were similar across the rostral and caudal AVCN. Cross sectional area, postsynaptic density length and curvature, and mitochondrial volume fraction were similar for axosomatic auditory nerve terminals, although rostral auditory nerve terminals contained a greater concentration of synaptic vesicles near the postsynaptic densities. These data demonstrate regional differences in synaptic organization of inputs to mouse bushy cells rather than the morphological characteristic of the cells themselves.